Confucian Local Wisdom in English Teaching: Higher Education Lecturers' Views on Engaging Z Generation - Lenny Marzulina; Meirizal; Farida; Hartono; Sardianto Markos Siahaan (Universitas Sulawesi Barat, 2025)
The purpose of this study is to find out how university instructors feel about incorporating Confucian local knowledge into English Language Teaching (ELT) for Generation Z students in higher education. Semi-structured interviews were used to gather data from six English lecturers at universities in Palembang, South Sumatra, using a qualitative case study design. Six interrelated themes emerged from the thematic analysis of Sumatra: the perceived applicability of Confucian values, pedagogical modifications for Generation Z, integration practices in ELT, implementation difficulties, lecturer beliefs and professional identity, and student. The results showed that when reframed to fit the traits and expectations of digital-native students, Confucian values like discipline, humility, respect for teachers, and lifelong learning remain pedagogically relevant. Various strategies, such as cross-cultural comparisons, the use of digital media, and storytelling, were employed by lecturers to render traditional wisdom accessible and meaningful. In addition to student resistance, curriculum inflexibility, and institutional constraints, the consistent application of value-based pedagogy was complicated by several challenges. The study emphasizes the dual function of lecturers as cultural mediators and language instructors who mediate conflicts between traditional values and modern learning environments. It is concluded that the integration of Confucian local wisdom in ELT not only improves linguistic proficiency but also cultivates ethical and intercultural awareness. This information contributes to the ongoing conversation regarding the localization of ELT practices in higher education, lecturer agency, and culturally responsive pedagogy.